2019
DOI: 10.1177/0300060519836305
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to antibiotic-associated diarrhea in patients in the intensive care unit receiving antifungals: a single-center retrospective study

Abstract: Objective To analyze factors related to antibiotic-associated diarrhea (AAD) in patients in the intensive care unit (ICU) receiving antifungals with the aim of informing rational antibiotic use. Methods Sex, age, medical history, use of proton pump inhibitors, administration of parenteral nutrition, albumin level, occurrence of AAD, type of antibiotics, duration of ICU admission, and prognosis were retrospectively analyzed. The associations of age, sex, medical history, and other factors with AAD were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A recent retrospective study has revealed a higher incidence of antifungal-associated diarrhea (AAD) in patients within the intensive care unit who were treated with antifungals. This outcome is likely attributed to the fact that antifungals are commonly administered alongside other antibiotics, increasing the likelihood of inducing AAD [ 37 , 38 ]. In our study, amphotericin b and fluconazole were the existing antifungals in the antibiotics that met the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study has revealed a higher incidence of antifungal-associated diarrhea (AAD) in patients within the intensive care unit who were treated with antifungals. This outcome is likely attributed to the fact that antifungals are commonly administered alongside other antibiotics, increasing the likelihood of inducing AAD [ 37 , 38 ]. In our study, amphotericin b and fluconazole were the existing antifungals in the antibiotics that met the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%